Depressive and anxiety symptoms, and their associated factors among adult, visually impaired follow-up patients attending the Hawassa University Comprehensive Specialized Hospital Eye Care and Training Center, South Ethiopia, 2024 - Beza Feleke Wube; Yezinash Addis; Biruk Fanta Alemayehu; Seblework Adugna Etsub; Biruk Lelisa Eticha (PLoS ONE, 2025)
Background Although the burden of depressive and anxiety symptoms among visually impaired adults has become a serious current health issue, relatively little is known in the study setting and in Ethiopia as well. This study aimed to assess the magnitude of depressive symptoms, anxiety, and their associated factors among adult, visually impaired follow-up patients of the Hawassa University Comprehensive Specialized Hospital Eye Care and Training Center, South Ethiopia, 2024. Methods From 10 June to 2 August 2024, an institution-based cross-sectional study was conducted on 518 study subjects using a stratified sampling technique. Data were collected using a pretested, structured, and interviewer-administered questionnaire. The Hospital Anxiety Depressive symptoms Scale was used for assessment of depressive and anxiety symptoms among the study subjects in this study. This validated tool is composed of 14 items (7 for depressive symptoms and 7 for anxiety). The clinical and visual impairment related characteristics was extracted from their medical recording chart in daily basis. The statistical package for social science version 26 was used to analyze the data. Binary logistic regression was fitted. Variables with a p-value less than 0.05 were considered statistically significant. Results From 518 visually impaired follow-up patients who participated in the study, about 34.9% (95% CI: 29.3–41.3) and 39.4% (95% CI: 35.1–43.8) experienced some level of depressive symptoms and anxiety symptoms, respectively. Social support, levels of visual impairment, a history of eye surgery, the pattern of vision loss, and patient satisfaction with an eye care service were variables significantly associated with both depressive and anxiety symptoms. Conclusion and recommendations Relatively higher burdens of depressive and anxiety symptoms were observed in study subjects. Screening common mental disorders during assessment of visual impairment is helpful. To enhance people's general health, public health programs must primarily target the most vulnerable populations.